Caught by the police: the life story of Dr. Anandswarup Gupta - "Gupta, Anandswarup...[etal]" (New Delhi, 2015)
Caught by the Police is the story of a talented, public-spirited and erudite man, with a multidimensional personality, a republican bent of mind, Indian values and English sensibilities. this book provides a unique account of the last decades of British Rule and the emergence of a new India.
Keywords: Indian Air Force